“Orientalizing” Art in Anatolia (8th–6th Centuries B.C.) - Kisbali, Tamás Péter (Actual Problems of Theory and History of Art, 2019)
The period between 8th–6th centuries B.C. in Anatolia was marked by the emergence of the Phrygian and Lydian kingdoms. Their material culture included not only items produced in local traditions (furniture, textiles) but also artifacts showing exotic tastes of the elites, following “oriental” examples (such as bronzes and ivories). In this paper, I examine some artistic tendencies of Phrygia and Lydia in the framework of today’s debates about the phenomenon of “orientalization”. The term “orientalization” was initially introduced to describe the style of objects with “oriental” motifs created according to the prototypes imported into the art of Greece. Subsequently, however, many other Hellenic phenomena of artistry, culture and social life became to be considered as “orientalization.” During the last decades, the term has been often discussed and reviewed. The scope of analysis was extended to the entire Mediterranean region throughout the 8th–7th centuries B.C., focusing on long-range elite interactions: a horizon of “orientalizing” material culture, stretching “from Assyria to Iberia.” However, the place and role of the cultures of Anatolia (mainly Phrygia and Lydia) in this system need to be defined in more detail. The Anatolian royals and elites maintained their own channels of connections with the core sources of “orientalizing” objects (North Syrian artistic centers and the Assyrian Empire). The tastes of Phrygian and Lydian elites were selective, so local artisans not only reproduced but also reinterpreted the prototypes they had had access to. In this paper, I aim to show how, on the one hand, the kingdoms of Anatolia were integrated into the elite networks of the 1st millennium B.C., while, on the other hand, displaying their own version of the “orientalizing” phenomenon.